QUALITY OF NATURAL COFFEE DRIED UNDER DIFFERENT TEMPERATURES AND DRYING RATES - Borém, Flávio Meira; Isquierdo, Eder Pedroza; Alves, Guilherme Euripedes; Ribeiro, Diego Egídio; Siqueira, Valdiney Cambuy; Taveira, José Henrique da Silva (Coffee Science - ISSN 1984-3909, 2018)
The final quality of coffees depends on the preservation of the cell membranes of the coffee beans, which can be damaged during the drying. Thus, the aim of this study was to assess the immediate and latent effects of the air temperature and drying rate on the sensorial quality of natural coffees, as well as its relationship with the chemical e physiological characteristics of the coffee beans. Mature fruits of arabica coffee were harvested and sundried to moisture content of approximately 35% (wb) and then moved into a mechanical drier under different conditions of drying. This process involved the combination of three dry bulb temperatures – DBT (35°C, 40°C, and 45°C) and two dew point temperatures – DPT (2.6°C and 16.2°C). Thus, the relative humidity of the air used for drying was a dependent variable of DTB and DPT, and as consequences, different drying rates were achieved for each DBT. The increase in the drying rate for the temperatures 35°C and 40°C has a negative effect on the final quality of natural coffee beans. However, for the temperature of 45°C, the effects of the drying rate on the coffee beans are overlaid by the thermal damages that are caused at this level of heating. Higher sensory scores for coffee are linked to lower values of electrical conductivity and potassium leaching of the exudate of the coffee beans, as well as lower values of fatty acids. It is emphasized that while the temperature of 35º C is recommended for the production of specialty coffees the temperature of 45º C is not.